2012
DOI: 10.1007/s11010-012-1254-6
|View full text |Cite
|
Sign up to set email alerts
|

β-1,4-Galactosyltransferase I involved in Schwann cells proliferation and apoptosis induced by tumor necrosis factor-alpha via the activation of MAP kinases signal pathways

Abstract: β-1,4-galactosyltransferase-I (β-1,4-GalT-I) plays a critical role in the initiation and maintenance of peripheral nervous system inflammatory reaction. However, the exact function of β-1,4-GalT-I in the regulation of SCs proliferation and apoptosis remains unclear. In this study, we found that low concentration of tumor necrosis factor-alpha (TNF-α) induced SCs proliferation, while high concentration of TNF-α induced SCs apoptosis. Meanwhile, the expressions of β-1,4-GalT-I, TNFR1, and TNFR2 were changed foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…TNF-induced βGalT1 expression has been demonstrated in vitro in astrocytes, Schwann cells and fibroblast-like synoviocytes [10][12]. To study the effect of TNF on βGalT1 expression in vivo , we injected CT mice with TNF, isolated ileum mucosa and examined βGalT1 gene expression by qPCR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TNF-induced βGalT1 expression has been demonstrated in vitro in astrocytes, Schwann cells and fibroblast-like synoviocytes [10][12]. To study the effect of TNF on βGalT1 expression in vivo , we injected CT mice with TNF, isolated ileum mucosa and examined βGalT1 gene expression by qPCR.…”
Section: Resultsmentioning
confidence: 99%
“…Links between tumor necrosis factor (TNF), a very potent proinflammatory molecule and a key signaling component of the immune system [9] and βGalT1 expression are known. First, stimulation of several cell types with TNF in vitro increases βGalT1 expression [10][12]. Second, i n vivo , spinal cord contusion injury as well as injection of LPS into the spinal cord induce βGalT1 expression, and it was suggesting that TNF might play a role in regulating βGalT1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, B4GALT1 has been strongly linked with multidrug resistance (8,16), tumor sensitivity to cisplatin (17,18) and promotion of cell death signaling pathways (19). Additionally, the gene undergoes promoter methylation in several cancer types and consequent silencing of the gene (13,20,21).…”
Section: Multifaceted Roles Of 5'-regulatory Region Of the Cancer Assmentioning
confidence: 99%
“…Tumor necrosis factor-α (TNFα) is a multipotent inflammatory cytokine that induces a wide variety of responses including apoptosis and proliferation, Yuan et al reported that low concentration of TNFα induced SCs proliferation, while high concentration of TNFα induced SCs apoptosis in vitro [18]. Here, TUNEL assay was used to detect apoptotic cells in the primary SCs treated with high concentration of TNFα (50 ng/ml).…”
Section: Resultsmentioning
confidence: 99%